School Adaptation Character Development Policy to Support Halal Tour in East Lombok Regency (Case Study at Senior High School in East Lombok Regency) - Sati, Lilis (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to provide guidance on the development of school adaptation character in East Lombok Regency to support halal tourism. The method used was a mixed method with data collection conducted by Purposive Sampling and Analytical Hierarchy Process (AHP). The results and discussion of alternative policy direction of adaptation character development of school of East Lombok Regency, West Nusa Tenggara Province, Indonesia are: (1) Religious with activity form that is: Hafidz Al-Qur'an at tourist place (2) Creative with activity form that was: Creating souvenir from Islamic nuanced materials on skill subjects (3) Caring for Environment with the form of activities that was: Make the slogans of environmental care in a place that has an important role in the development of character adaptation to support halal tourism in the district of East Lombok.